PPIH is a novel diagnostic biomarker associated with immune infiltration in cholangiocarcinoma - Jun Ye; Zhitao Chen; Chuan Zhang; Rui Xie; Haini Chen; Peng Ren (BMC Cancer)
Abstract Background Cholangiocarcinoma (CHOL) is the second most common primary liver malignancy, characterized by high aggressiveness and heterogeneity. It is typically diagnosed at an advanced stage, leading to a poor prognosis. Although Peptidyl Proline Isomerase H (PPIH) has been implicated in various tumors, its role in CHOL remains unexplored. This study aims to investigate the diagnostic value and potential function of PPIH in CHOL. Methods We analyzed the expression levels, prognostic significance, and diagnostic efficiency of PPIH in CHOL using data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) datasets, coupled with gene enrichment analyses. The CIBERSORT database was employed to assess the correlation between PPIH expression and immune cell infiltration in CHOL. Additionally, immunohistochemical experiments were conducted to validate PPIH expression levels in CHOL tissues and to explore its correlation with TP53 gene mutations. Results Our findings indicate that overexpression of PPIH mRNA in CHOL is associated with poor prognosis, with increased PPIH protein levels observed in CHOL tissues. Furthermore, PPIH expression showed a positive correlation with TP53 mutations. PPIH demonstrated strong diagnostic value for CHOL. Moreover, PPIH may influence tumor progression through its involvement in cell cycle regulation and spliceosome pathways, and is associated with immune cell infiltration levels. Conclusion The results of this study suggest that PPIH is a potential novel biomarker with significant diagnostic value for patients with CHOL. PPIH may also play a role in modulating the immune microenvironment, contributing to poor prognosis.